Clinical Application of Platelet-Rich Fibrin in Pediatric Dentistry - Gunasekaran, Sowndarya; Sakthivel, Soundarya; M., Shanthala B.; Babu, George; Vijayan, Vidhya (Journal of Health and Allied Sciences NU, 2021)
Platelet-rich fibrin (PRF) is a fibrin matrix in which platelet cytokines, growth factors, and cells are trapped and may be released after a certain time and that can serve as a resorbable membrane. It can be obtained from blood with the help of a simple process. PRF is basically a concentrate of growth factors that promote wound healing and regeneration, which is used in various disciplines of dentistry to repair various lesions and regenerate dental and oral tissues. Although the use of PRF is well-documented, its use in pediatric dentistry remains unexplored, due to its restrictions and on account of the fact that it is a blood-derived product. PRF has been used globally to enhance tissue healing. This article provides an insight into the use of PRF in pediatric dentistry, its benefits, limitations, and recommendations.
Keywords: apexogenesis; direct pulp capping; regenerative endodontics; scaffolds; platelet-rich plasma